Association between infant and child feeding index (ICFI) and nutritional status of 6-23 month-old Filipino children in five cities and three municipalities - Panlilio, Maria Luisa C. (2015.)
The adequacy of feeding directly affects the nutritional status of children below 23 months of age. Improving feeding practices is therefore critical to good nutrition, health and development. One cannot however single out an indicator and relate it directly to health outcomes since feeding practices are multi-dimensional and age-specific. These indicators therefore should be considered together as an index (i.e., ICFI) to provide a relevant measure of feeding practices that could be interpreted easily and used effectively for communication and monitoring.This investigation aimed to determine the association between Infant and Child Feeding Index (ICFI) and nutritional status of children 6-23 months of age in five cities and three municipalities of the Philippines. Specific associations were sought for ICFI and underweight, stunting, and iron deficiency anemia. An analytic cross-sectional study design was used in this investigation. Secondary data from the 2011 baseline study of Saniel et al were used.
Available in CD, pdf copy.
Thesis (Master of Science in Public Health, Nutrition)--University of the Philippines Manila.
Keywords: Infants -- Nutrition; Children -- Nutrition; Infant and Child Feeding Index